2006
DOI: 10.1523/jneurosci.4531-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2-Mediated Microglia/Astrocyte Interaction Enhances Astrogliosis and Demyelination intwitcher

Abstract: Prostaglandin (PG) D 2 is well known as a mediator of inflammation. Hematopoietic PGD synthase (HPGDS) is responsible for the production of PGD 2 involved in inflammatory responses. Microglial activation and astrogliosis are commonly observed during neuroinflammation, including that which occurs during demyelination. Using the genetic demyelination mouse twitcher, a model of human Krabbe's disease, we discovered that activated microglia expressed HPGDS and activated astrocytes expressed the DP 1 receptor for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
142
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 62 publications
4
142
0
Order By: Relevance
“…We found previously that both L-PGDS (Taniike et al, 2002) and HPGDS (Mohri et al, 2006) were upregulated together with specific elevation of PGD 2 in the brains of twitcher mice, a model of chronic neuroinflammation. Suppression of HPGDS-PGD 2 -DP 1 signaling resulted in the clinicopathological improvement in twitcher (Mohri et al, 2006).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…We found previously that both L-PGDS (Taniike et al, 2002) and HPGDS (Mohri et al, 2006) were upregulated together with specific elevation of PGD 2 in the brains of twitcher mice, a model of chronic neuroinflammation. Suppression of HPGDS-PGD 2 -DP 1 signaling resulted in the clinicopathological improvement in twitcher (Mohri et al, 2006).…”
Section: Introductionmentioning
confidence: 84%
“…HPGDS knock-out (H-KO) (Mohri et al, 2006), L-PGDS knock-out (L-KO) (Eguchi et al, 1999), and DP 1 knock-out (DP 1 -KO) (Matsuoka et al, 2000) mice were generated by standard gene targeting technology with embryonic stem cells derived from the 129 strain of mouse. H-KO, L-KO, and DP 1 -KO mice were backcrossed to the inbred C57BL/6J strain 15 times.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, it has been suggested that prostaglandin D 2 (PGD 2 ) contributes to astrocyte-derived toxicity. 5 Interestingly, it has been demonstrated that the genetic or pharmacological inhibition of the PGD 2 /PGD 2 receptor signaling markedly reduced astrogliosis, 30 IFNc triggers a motoneuron-selective death pathway J Aebischer et al tion whether PGD 2 function directly on motoneurons as a death trigger and/or indirectly by consolidating the inflammatory phenotype of mutant astrocytes. In the present study, we show that inhibition of IFNg activity by antagonist antibodies greatly improves the survival of motoneurons cocultured with mutant astrocytes, whereas blocking the interaction between LIGHT and LT-bR by LT-bR-Fc produced a more moderate improvement in motoneuron survival.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were approved by The University of Tokyo's Institutional Animal Care and Use Committee. Five-to eight-week-old female H-PGDS À / À (C57BL/6 and Balb/c) and littermates control mice or CXCR4 flox/flox mice (C57BL/6) were generated and bred as described previously 49,50 . Four-week-old female Kit W-sh/W-sh (C57BL/6) mice were generously provided by RIKEN BioResource Center.…”
Section: Methodsmentioning
confidence: 99%